The Impact of Positive Self-Talk on the Self-Confidence Levels of East Java Wushu Athletes - Boy, Muhammad Daffa Golden; Ridwan, Mochamad; Prihanto, Junaidi Budi (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The purpose of this study was to examine how positive self-talk affects the self-confidence levels of East Java wushu athletes. This study used a quantitative approach with a single-group pretest-posttest pre-experimental design. Purposive sampling was used to select 23 senior wushu athletes who met the inclusion criteria. The data collection method was the Athlete Self-Confidence Scale, which was based on Bandura’s self-efficacy theory and had been tested for reliability and content validity with a Cronbach’s Alpha value of at least 0.7. Over four weeks, positive self-talk intervention was provided through eight training sessions that focused on cognitive regulation and positive affirmations. There was a significant difference between pretest and posttest scores (p < 0.001), with a very large effect size (Cohen’s d = 8.70), after data analysis using a paired sample t-test. The results indicate that positive self-talk significantly improves the self-confidence of wushu athletes. These findings highlight the importance of using psychological strategies in athlete training, especially in sports such as wushu, which require mental stability and high concentration.